Fish drying machine with PV system for fisherman to support blue economy - I Gusti Made Ngurah Desnanjaya; I Komang Arya Ganda Wiguna; I Made Aditya Nugraha (Bulletin of Electrical Engineering and Informatics, 2023)
The abundance of fish catches in Indonesia is excellent potential. Still, if the abundant results cannot be adequately managed and are just wasted, it will eventually lead to bad things. This problem was also found in Seraya village, Karangasem, Bali, where large fish yields and the fish processing process were still constrained by weather and environmental conditions causing the expected results to not be achieved. To overcome this, a photovoltaic (PV) system-based fish dryer was developed that can assist the fish drying process. Utilization of this system is also supported by good solar energy potential. The system can generate 402.78 Wh of electrical energy per day, covering 104.89% of the electrical energy demand of the fish dryer. The results of statistical tests using the Mann-Whitney test for fish weight and unpaired t-test for fish moisture content showed no significant results (p0.05). This value states that there is no difference in the results of drying fish with the PV system and the traditional method. From this, we can conclude that fish drying using a solar power system works similarly to conventional fish drying methods.